Study on Performance Evaluation of Tubular Maize Sheller under Frontline Demonstration - Pongen, Longma Yanger (Current Topics in Agricultural Sciences Vol. 2, 2021)
The paper aims to study the Performance Evaluation of Tubular Maize sheller under Frontline Demonstration in comparison to farmers’ practice of using finger tips and thumb pressing. Technology developed by CIAE Bhopal was used as Action Research Participatory Approach carried out during 2016-2019 in Kohima district of Nagaland. The demo involved 150 beneficiaries belonging to small and marginal Socio Economic Status. Farmers after maize harvest sundry and later stacked above the fireplace for smoke drying in traditional kitchen to minimize the moisture content and protect the seed from pest which has been the tradition for years. The demonstration results showed that, shelling capacity of tubular maize sheller (31.36 kg/hr) was twice as much as that of farmers practice (13.11 kg/hr) indicating percentage increase by 140%, i.e. increase in shelling percentage over the years from 92-177%. It also highlighted an efficiency of 99. 69%, Cost of shelling one quintal of maize to be` 171.58 indicating a saving of nearly 60% against hand shelling. Feedback views on the Technology were recorded and assigned rank according to responses, of the eight statement four statement were ranked one on the basis of weighted mean such as No special training required for handling the maize sheller, avoids injury to fingers during use, reduce drudgery during handling and women friendly tool. Rank two was obtained for saves time and energy, Rank three was assigned towards the statement that it avoids irritation of eyes, nose, mouth during shelling, Rank four was in favour of convenient to operate, use and handle. Few (6 Nos) had the opinion in modifying and standardising the sheller as the local maize cultivars were larger in circumference than the demonstrated Technology. Chi-square testing of Tubular sheller (x=33.2) proves that its performance is significantly different from hand shelling p<0.05.